Traditional Anti-Covid Herbal Anti-Bokek Preservation of Local Drinks - Ana Theriana; Idan Shalahuddin; Yuspita Sari; Elvina Kamelia Ulfa (CV. AGUSPATI RESEARCH INSTITUTA, 2021)
Pulau Panggung Village, Semende Darat Laut Subdistrict, which is located in Muara Enim Regency, South Sumatra Province, the majority of people are Muslim and still highly respect the customs of their village In general, people still depend on their livelihoods from agricultural products, gardens, rice fields and casual laborers. There are still many people who find it difficult to work meet daily needs and finance education for children. Since the COVID-19 pandemic hit all capital cities and regions In Indonesia, the learning system began to change into an online or virtual system and all gradually use sophisticated tools such as cellphones, laptops and mobile phones there are many more, not to mention the use of quota packages to open internet and device applications on android so that many parents feel difficult to meet their child's learning needs. Now people really hope that there will be input assistance to increase knowledge in order to eradicate poverty and be able to generate new business as their side income.